2022
DOI: 10.1038/s41467-022-28778-8
|View full text |Cite
|
Sign up to set email alerts
|

Measuring protected-area effectiveness using vertebrate distributions from leech iDNA

Abstract: Protected areas are key to meeting biodiversity conservation goals, but direct measures of effectiveness have proven difficult to obtain. We address this challenge by using environmental DNA from leech-ingested bloodmeals to estimate spatially-resolved vertebrate occupancies across the 677 km2 Ailaoshan reserve in Yunnan, China. From 30,468 leeches collected by 163 park rangers across 172 patrol areas, we identify 86 vertebrate species, including amphibians, mammals, birds and squamates. Multi-species occupanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 81 publications
0
16
0
Order By: Relevance
“…There have been numerous recent studies that have validated and calibrated iDNA techniques for terrestrial mammal monitoring. For example, leeches have been used for occupancy modelling of vertebrate species (Ji et al., 2022) because they rarely move outside a very narrow range, which makes it possible to estimate occurrence ranges accurately. However, leeches are found in limited climatic and habitat zones (Abrams et al., 2019)—typically wet and tropical—meaning that using leech iDNA in drier environments may not be possible.…”
Section: Introductionmentioning
confidence: 99%
“…There have been numerous recent studies that have validated and calibrated iDNA techniques for terrestrial mammal monitoring. For example, leeches have been used for occupancy modelling of vertebrate species (Ji et al., 2022) because they rarely move outside a very narrow range, which makes it possible to estimate occurrence ranges accurately. However, leeches are found in limited climatic and habitat zones (Abrams et al., 2019)—typically wet and tropical—meaning that using leech iDNA in drier environments may not be possible.…”
Section: Introductionmentioning
confidence: 99%
“…While eDNA-based approaches may allow for relatively rapid sampling, it often requires weeks or months of laboratory work, and species identifications can be limited by primer biases and DNA reference databases. Moreover, only freshwater eDNA (Ushio et al, 2018) and iDNA from bulk arthropod samples and leeches (Ji et al, 2022;Lynggaard et al, 2019;Lynggaard, Oceguera-Figueroa, et al, 2022) have been found applicable for bird detection.…”
Section: Vertebrate Taxa Detected Using Airborne Ednamentioning
confidence: 99%
“…Environmental DNA is frequently leveraged in aquatic systems where its use for biomonitoring is widespread, and is often employed to meet regulatory obligations, which arise both commercially and from public bodies (Deiner et al, 2016; Ficetola et al, 2008; Rees et al, 2014; Ruppert et al, 2019). Aquatic eDNA is commonly used to survey diversity in freshwater and marine ecosystems (Díaz‐Ferguson & Moyer, 2014; Thomsen & Willerslev, 2015), and has been applied in more complex ecological analyses such as occupancy modeling (Schmelzle & Kinziger, 2016), monitoring protected area efficacy (Ji et al, 2022) and understanding depth partitioning (e.g., in freshwater lakes fish eDNA appears stratified reflecting thermal niches, Littlefair et al, 2020, and kelp forests, Monuki et al, 2021).…”
Section: Introductionmentioning
confidence: 99%